PENINGKATAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN STRATEGI GIVING QUESTION AND GETTING ANSWSER PADA SISWA KELAS X2 SMA NEGERI 1 BENAI TAHUN AJARAN 2011/2012 - Arnentis '; Wan Syafi’i; Desti Nurfa Dila (Biogenesis, 2012)
This study aims to increase the activity and student learning outcomes through the implementation of cooperative learning model by giving answer to the question and getting the class X2 Benai SMA N 1 academic year 2011/2012. This research is a class action, which was conducted in January-February 2012. Subjects were high school students X2 N 1 Benai class numbering 36 people, consisting of 16 men and 20 women. Parameter studies are student activities and learning outcomes which consists of studying the absorption and completeness. Average student activity on the cycle I is 74.87% (enough) and increased in the second cycle is 81.28% (good). Average absorption of students in the cycle I is 78.94 (enough) and the second cycle which had an average of 80.42 (good). Thoroughness of student learning in the cycle I was 91.67% (excellent) and 97.22% (excellent) on the second cycle. I cycle a group award in any super group 4 and 3 great group and the second cycle of all groups received a great award. From the research results can be concluded that the use of cooperative learning models by giving a strategy question and getting answer can increase the activity and students' high school class X2 N 1 Benai in the academic year 2011/2012.Keywords: Activities, Cooperative learning, Learning outcomes, The strategy giving question and getting answer.